2018
DOI: 10.1097/md.0000000000011345
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum leptin levels and breast cancer risk

Abstract: Background:Many studies have indicated that leptin is correlated with breast cancer occurrence and tumor behavior. However, this issue remains controversial. Therefore, we conducted an updated meta-analysis to investigate the role of leptin in breast cancer.Methods:We performed a systematic literature search and identified relevant papers up to 1 September 2017. Standardized mean differences (SMDs) with 95% confidence intervals (CIs) were used to evaluate effect sizes.Results:Thirty-five eligible studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 47 publications
3
57
2
1
Order By: Relevance
“…In addition, this adipokine is able to reduce the effectiveness of antineoplastic molecules such as 5-fluorouracil, taxol, or vinblastine, as well as antiestrogens such as Tx [23]. Clinical studies confirmed a positive association between serum leptin levels and breast cancer risk particularly in overweight/obese women [24]. However, our results did not show the involvement of leptin in the resistance of hormonal therapies in our model.…”
Section: Discussioncontrasting
confidence: 54%
“…In addition, this adipokine is able to reduce the effectiveness of antineoplastic molecules such as 5-fluorouracil, taxol, or vinblastine, as well as antiestrogens such as Tx [23]. Clinical studies confirmed a positive association between serum leptin levels and breast cancer risk particularly in overweight/obese women [24]. However, our results did not show the involvement of leptin in the resistance of hormonal therapies in our model.…”
Section: Discussioncontrasting
confidence: 54%
“…Current data regarding to the association between serum leptin levels and MT development are controversial. Some studies suggested high levels of serum leptin as a biomarker for breast cancer development [27,28]. Since we determined no significant difference in serum leptin levels between MT-positive and MT-negative mice, our results are in accordance with the previous studies reporting no correlation between serum leptin levels and breast cancer development [14,16,25].…”
Section: Discussionsupporting
confidence: 92%
“…Mice with adipose MCP1 deficiency exhibited lower plasma concentrations of PAI1, leptin, and resistin, particularly those fed the HFD. PAI1 (34,35), leptin (36,37), and resistin (38,39) are proinflammatory cytokines with demonstrated cancer-promoting potential. Depletion of PAI1 inhibited spontaneous metastasis of LLC (33), knockout of leptin receptors mitigated mammary tumorigenesis mediated by mouse mammary tumor virus (40), and inhibition of resistin expression suppressed experimental metastasis of chondrosarcoma in mice (41).…”
Section: Discussionmentioning
confidence: 99%